2019
DOI: 10.1080/00344893.2019.1682648
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Importance of Localness for MP Campaigning and Legislative Performance

Abstract: Understanding how MPs use ties to their constituency, or localness, is important for understanding the nature of the MP-constituency relationship. MPs are expected to actively focus on their constituency in their work to help their campaign and gain reelection. To explore the relationship between MPs and the use of localness we examine the use of localness in their legislative activity. Combining the focus on constituency and parliamentary behaviour data is not often done and we utilise a dataset allowing us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Similarly, there is little evidence that British MPs who are local actually perform better in the role, whatever voters might think (Sallberg and Hansen, 2020). The rise of the constituency role, for example - with MPs spending an increasing amount of their time on matters to do with their constituency - has been pretty much universal over the last 40 or so years and there is not much evidence that native sons or daughters do it better than those from outside the area.…”
Section: Does ‘Being Local’ Matter?mentioning
confidence: 99%
“…Similarly, there is little evidence that British MPs who are local actually perform better in the role, whatever voters might think (Sallberg and Hansen, 2020). The rise of the constituency role, for example - with MPs spending an increasing amount of their time on matters to do with their constituency - has been pretty much universal over the last 40 or so years and there is not much evidence that native sons or daughters do it better than those from outside the area.…”
Section: Does ‘Being Local’ Matter?mentioning
confidence: 99%
“…However, there are also null findings in the literature. For instance, Fiva, Halse, and Smith (2018) leveraged close elections in Norway between 1953 and 2013 and found that representatives did not increase the level of investment in their hometown, and Sällberg and Hansen (2020) found that localness was unrelated to the number of constituency mentions in the UK House of Commons over the 2015/2016 constituency session. Henceas with other aspects of the 'politics of presence' (Preuhs 2005) the literature suggests that descriptive representation does not automatically translate into policy representation; rather, the relationship can be contextual and contingent on institutional factors.…”
Section: In Southern Politicsmentioning
confidence: 99%
“…Localness has informed several lines of inquiry in the comparative literature. Perhaps, the dominant strand has analysed the impact of MP localness on legislative performance (Sällberg and Hansen 2020). In France, for example, the cumul has been widely implicated in the weak legislative performance of National Assembly deputés when evaluated in terms of their attendance at plenaries and committee sessions (Navarro et al 2012;Brouard et al 2013;Daoulas 2021) although, plainly, absenteeism of this kind is not the only or necessarily the best measure of legislative efficiency (Hajek 2017; van der Voorde 2020; Van de Voorde and de Vet 2020).…”
Section: Perspectives On Mp 'Localness'mentioning
confidence: 99%